Predicted facies, sedimentary structures and potential resources of Jurassic petroleum complex in S-E Western Siberia (based on well logging data); IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Prakojo F. S. Feliks Santo (Geophysical Surveying Methods for Ore Deposit Prospecting. Geoinformation Systems in Geophysical Surveys, 2015)
Title screen